Missing population studies on the new European Standard set loci (ESS) and its impact on population statistics. (December 2015) - Emmerova, Barbora; Ehler, Edvard; Vanek, Daniel
Abstract: We have encountered a decrease in the number of population studies published in recent years. Allelic frequencies for the new European standard set of loci (D12S391, D1S1656, D2S441, D10S1248, and D22S1045) are not published for many countries. This can lead to bias in statistical evaluation of DNA typing results.